Therapeutic Potential of PSC-derived Cell Transplantation in Parkinson's Disease: A Systematic Review and Meta-analysis of Preclinical Studies - Karimi, Aliasghar; Shiri, Zahra; Tabrizi, Reza; Naderi, Somayeh; Salahi, Sarvenaz; Elmi, Mitra; Baharvand, Hossein (Current Stem Cell Research & Therapy, 2025)
<span class=
Keywords: Parkinson' s disease